The Effect of Tik Tok Social Media Use on Adolescent Mental Health - Rifqi Yoke Sopyan Arief (Riviera Publishing, 2025)
This study aims to explore the impact of TikTok social media use on the mental health of adolescents at SMAN 1 Pangandaran, West Java. TikTok, now one of the most popular social media media platforms among adolescents, offering a variety of content that has the potential to influence how adolescents interact with their social world and construct personal identities. The method used in this study was a qualitative case study approach, where data was obtained through in-depth interviews and direct observation of students at the school. The results revealed that TikTok has both positive and negative impacts on adolescent mental health. Positively, TikTok provides a platform for adolescents to express themselves, find a supportive community, and access useful information for personal development. However, more prominent negative impacts are the emergence of social anxiety, detrimental self-comparison, and pressure to gain recognition through the number of followers and interactions received on the platform. This study also shows that excessive scrolling habits have the potential to disrupt sleep quality and lead to other psychological disorders. While TikTok can be a positive platform for self-expression and learning, its negative impacts require more serious attention, particularly those related to social anxiety and self-dissatisfaction. Recommendations in this study include the importance of wise use TikTok by teenagers, the development of features that better support mental health by developers, and the need for parents and educators to provide more in-depth education on how to use social healthily media.